A CRISPR mediated point‐of‐care assay for the detection of mucosal calprotectin in an animal model of ulcerative colitis - Selena Chia; Tianruo Guo; Ewa M. Goldys; Sophie C. Payne; Wenlu Duan; Nigel H. Lovell; Mohit N. Shivdasani; Fei Deng (Bioengineering & Translational Medicine)
Abstract Inflammatory bowel disease (IBD) is a chronic disorder associated with inflammation in the gastrointestinal tract, leading to a range of debilitating symptoms. Fecal calprotectin is an established biomarker for ulcerative colitis (UC), one of the main IBD diseases, which provides indications of the presence and severity of inflammation in the digestive tract. Enzyme‐Linked Immunosorbent Assay (ELISA) as a gold standard approach for fecal calprotectin detection is time‐consuming and impractical in point‐of‐care settings. Moreover, obtaining fecal samples from patients is challenging and inhibits longitudinal monitoring. To address these specific problems, we have developed a novel approach for detecting calprotectin which leverages clustered regularly interspaced short palindromic repeats (CRISPR)/Cas technology. We successfully developed a portable tube‐based CRISPR/Cas assay for point‐of‐care testing of calprotectin. This assay showed a detection range from 1 to 10,000 ng/ml (over 4 log units), using both fluorescent and colorimetric analytical techniques. The established assay was further validated through measurements in mucosal samples obtained in an anesthetised preclinical rodent model of UC, with 2–3 times higher calprotectin concentration detected in UC rat samples compared to that of healthy control animals. This point‐of‐care test may provide a rapid, precise, and user‐friendly approach for the diagnosis and monitoring of IBD through mucosal sample testing.